Oedipism – case report and review - Kopacz, Dorota; Baran-Lego, Agnieszka; Maciejewicz, Piotr; Kopacz, Amelia H. (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Oedipism is the term describing autoenucleation – the most dramatic form of eye self-mutilation. It belongs to so called major form of self-injurious behaviors as well as wirst-slashing, autocastration or head banging. In the majority of cases it occurs during acute or chronic psychoses with accompanying visual and/or auditory hallucinations. We present a case of a 32 year-old man with diagnosed bipolar illness, who pulled out his eye during a psychotic episode with accompanying both visual and auditory disorders. At Emergency Department urgent laboratory tests, CT examination of the head and facial skeleton, ophthalmological and neurological consultations were performed. Because there were no life-threating complications, after orbital wound surgical dressing he was transferred to the psychiatric hospital to estimate and start adequate treatment. Referring to this case we have prepared a review on the self-enucleation problem.